2007
DOI: 10.1111/j.1574-6941.2006.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Ciliate biogeography in Antarctic and Arctic freshwater ecosystems: endemism or global distribution of species?

Abstract: Ciliate diversity was investigated in situ in freshwater ecosystems of the maritime (South Shetland Islands, mainly Livingston Island, 63 degrees S) and continental Antarctic (Victoria Land, 75 degrees S), and the High Arctic (Svalbard, 79 degrees N). In total, 334 species from 117 genera were identified in both polar regions, i.e. 210 spp. (98 genera) in the Arctic, 120 spp. (73 genera) in the maritime and 59 spp. (41 genera) in the continental Antarctic. Forty-four species (13% of all species) were common to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 45 publications
3
37
1
Order By: Relevance
“…Finlay and Fenchel (2004) state that the cosmopolitan fraction of organisms in the bacterial size range is usually about 2.5-fold higher than detected in the present study. Cox et al (2016) also found a percentage of ∼35-60% cosmopolitan OTUs in Antarctic fungi and Petz et al (2007) showed that 13% of freshwater ciliate species were shared between the Arctic and the Antarctic. For larger organisms Griffiths et al (2009) suggest a general level of endemism of 50% in Southern Ocean benthos, and even greater levels of endemism (up to possibly 100% at species level) are reported across a range of Antarctic terrestrial biota Pugh and Convey, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Finlay and Fenchel (2004) state that the cosmopolitan fraction of organisms in the bacterial size range is usually about 2.5-fold higher than detected in the present study. Cox et al (2016) also found a percentage of ∼35-60% cosmopolitan OTUs in Antarctic fungi and Petz et al (2007) showed that 13% of freshwater ciliate species were shared between the Arctic and the Antarctic. For larger organisms Griffiths et al (2009) suggest a general level of endemism of 50% in Southern Ocean benthos, and even greater levels of endemism (up to possibly 100% at species level) are reported across a range of Antarctic terrestrial biota Pugh and Convey, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Only limited support was obtained for a systematic decrease in eukaryotic (primarily fungi, algae and protists) diversity with latitude (Lawley et al 2004;Petz et al 2007), that is, when the comparisons were made between maritime and continental Antarctic sites, whereas there was no evidence for a trend of decreasing diversity across the entire range of the maritime Antarctic. Similar findings were also reported for tardigrades and rotifers (Sohlenius & Boströ m 2005) and plants (Peat et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…In them we find an unique combination of ecological and biological properties. In addition to representing a major microbial component of every aquatic system also in the polar regions [1,2], they are facultative sexual organisms. Their life cycles in fact involve an optional alternation between periods of vegetative growth (mitotic multiplication) associated with availability of energetic resources from the environment, and sexual events associated with famine and other stressing conditions [3].…”
Section: Introductionmentioning
confidence: 99%